2009
DOI: 10.1093/humrep/dep193
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted gene pattern in patients with repeated in vitro fertilization (IVF) failure

Abstract: The evaluation of the endometrium of RIF patients by gene array analysis demonstrates that the expression of various genes is altered, including those belonging to the cell cycle, Wnt signaling and cellular adhesion pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 32 publications
6
95
0
Order By: Relevance
“…Endometrial transcriptomic profiles have also been investigated under different controlled ovarian stimulation protocols (Simon et al 2005;Horcajadas et al 2008), or in the context of unexplained pathologies such as recurrent implantation failure (Tapia et al 2008;Koler et al 2009;Altmäe et al 2010), or other endometrial conditions (Table 1) (Habermann et al 2011;Matsuzaki 2011). Most of these studies investigate the transcriptomic signature in the whole endometrial tissue without separating the different compartments.…”
Section: Transcriptomics Of the Endometriummentioning
confidence: 99%
“…Endometrial transcriptomic profiles have also been investigated under different controlled ovarian stimulation protocols (Simon et al 2005;Horcajadas et al 2008), or in the context of unexplained pathologies such as recurrent implantation failure (Tapia et al 2008;Koler et al 2009;Altmäe et al 2010), or other endometrial conditions (Table 1) (Habermann et al 2011;Matsuzaki 2011). Most of these studies investigate the transcriptomic signature in the whole endometrial tissue without separating the different compartments.…”
Section: Transcriptomics Of the Endometriummentioning
confidence: 99%
“…Several studies suggested that uterine receptivity is diminished during controlled ovarian hyperstimulation (COH) used in ART compared with natural cycles [13][14][15] . Although studies have shown alterations of molecules are related to endometrial receptivity in COH-treated subjects [16][17][18][19][20][21] , the impact of COH treatment on endometrial receptivity is still unclear.Homeobox (HOX) genes are the vertebrate homologs of the Drosophila homeotic selector genes, which contain a 60-amino acid homeodomain as a DNA-binding domain via a helix-turn-helix motif [22] . 31(4):535-542,2011 J Huazhong Univ Sci Technol[Med Sci]…”
mentioning
confidence: 99%
“…Using a specific primer for human Tert, real-time PCR was performed for investigating the mRNA level of Tert. Additionally, changes in ER alpha and PR expression were also analyzed as they are indispensible in embryo implantation (Carranza-Lira et al, 2000;Koler et al, 2009;Cha et al, 2012). Compared to the control, the RIF group showed a substantial increase in Tert expression and a significant reduction in ER alpha expression, whereas no evident change was observed in PR expression ( Figure 1A).…”
Section: Changes In Tert Er Alpha and Pr Mrna Expression During Implmentioning
confidence: 99%
“…In humans, the putative implantation window occurs at the mid secretory phase, and is precisely controlled by synergistic signals of progesterone and estrogen, which bind to the progesterone receptor (PR) and estrogen receptor (ER), respectively (Carson et al, 2000;Groothuis et al, 2007;Large and DeMayo, 2012). In the endometrium with recurrent implantation failure (RIF), approximately 8% of the downregulated genes are associated with compromised estrogen signals, due to decreased expression of ER alpha (Carranza-Lira et al, 2000;Koler et al, 2009). However, the molecular mechanisms responsible for recurrent implantation failure remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%